PERSEPSI WISATAWAN MANCANEGARA TERHADAP PELAYANAN BUTLER DI AKARA VILLAS KUTA - Ni Made Yeni Bahari; I Made Darma Oka (Institut Pariwisata dan Bisnis Internasional, 2014)
This article is based on research the perception of tourists to the butler’s service at Akara Villas in Kuta.This research is a combination of quantitative and qualitative data with tourism sociology approach. The data of tourists were collected by accidental random sampling with interview techniques combination, observation and adopting data from publication. The number of samples are used in this research is 70 respondents. According to the research’s finding (13 variables) the perception of tourists to the butler’s service who works at Akara Villas in Kuta is very good or very satisfying with the average score of 4.38. This means the butler’s service is necessary to be kept well and increased for the existence of Akara Villas in the future.